Penjatuhan Pidana Di Bawah Minimum Terhadap Pelaku Tindak Pidana Perzinahan: (Kajian Putusan Nomor:244/Pid.B/2017/Pn Lwk) - Isnin Harianti (Indonesian Journal of Criminal Law, 2019)
This study aims to analyze court decisions that decide the perpetrators of criminal acts of adultery with a sentence of at least 1 (one) month in prison. The problems that arise from this study are, first, is the judge's basis in making a sentence of a sentence of at least 1 (one) month imprisonment in the decision Number 244 / Pid.B / 2017 / Pn Lwk? Second, Is the decision of at least 1 (one) month imprisonment against the perpetrators charged with committing criminal adultery adhering to the value of justice? The research method uses a normative juridical approach. Data collection was carried out with literature review. The analysis is carried out qualitatively. The results showed: First, the consideration of judges in deciding a minimum sentence of 1 (one) month imprisonment to the perpetrator charged with committing a criminal act of adultery was based solely on the defendant's defendant who had not committed a crime and admitted his mistake. adultery with a minimum sentence of 1 (one) month imprisonment is not in accordance with the value of justice, because the judge must have believed that the defendant committed an adultery crime can decide ideally a third of criminal sanctions Article 284 of the Criminal Code, so that the judge does not seem to hesitate in ensnaring the perpetrator. Penelitian ini bertujuan untuk menganalisis putusan pengadilan, yang memutus pelaku tindak pidana perzinahan dengan hukuman minimal 1 (satu) bulan penjara. Permasalahan yang timbul dari kajian ini adalah, pertama, apakah dasar pertimbangan hakim dalam penjatuhan putusan hukuman minimal 1 (Satu) bulan penjara pada putusan Nomor 244/Pid.B/2017/Pn Lwk? Kedua, Apakah putusan minimal 1 (Satu) bulan penjara terhadap pelaku yang didakwa melakukan pidana perzinahan telah sesuai dengan nilai keadilan? Metode Penelitian menggunakan pendekatan yuridis normatif. Pengumpulan data dilakukan dengan kajian kepustakaan. Analisis dilakukan secara kualitatif. Hasil penelitian menunjukkan: Pertama, Pertimbangan hakim dalam memutus pidana minimum 1 (Satu) bulan penjara kepada pelaku yang didakwa melakukan tindak pidana perzinahan adalah hanya berdasar pada terdakwa terdakwa belum pernah melakukan tindak pidana dan mengakui kesalahannya, Kedua, putusan hakim yang memutus pelaku tindak pidana perzinahan dengan hukuman minimum 1 (Satu) bulan penjara belum sesuai dengan nilai keadilan, karena hakim seharusnya dengan telah yakin kepada terdakwa melakukan tindak pidana perzinahan dapat memutus idealnya sepertiga dari sanksi pidana Pasal 284 KUHP, sehingga tidak terkesan hakim ragu dalam menjerat pelaku tindak pidana perzinahan